Factors associated with subclinical atherosclerosis in HIV infected patients from northeast of Brazil - Burgos, Ursula Maria Moreira Costa (2021)
Introduction: AIDS has changed its morbidity curve, rising cardiovascular diseases. HIV-infected patients have increased cardiovascular event rates but data on the prevalence of subclinical atherosclerosis are not uniform. Methods: HIV-infected patients underwent to coronary tomography for CACs assessement. We performed a comparison between 97 HIV-infected patients and 129 seronegative healthy controls. The univariable analysis matched the association of HIV infection, cardiovascular risk profile, and HIV-related factors with subclinical atherosclerosis. Results: HIV-infected patients with CACs above zero were older (54.8±7.0 vs. 43.3.5±11.0 years; p<0.001) and more likely to have hypertension (36.7% vs. 12.5%; p=0.07) than HIV(-) CACs zero ones. Factors associated with altered CACs in unadjusted hazard ratio were age (HR=1.13; 95%CI=1.07-1.20; p<0.0001) and hypertension (HR=4.05; 95%CI=1.42-11.60; p=0.0009). When adjusted hazard ratio was constructed age, male gender and protease inhibitors (PI) use appeared as factors associated with coronary calcification. HIV-infected patients were less likely to have hypertension (20.2% vs 50.4%; p<0.001) and diabetes (5.3% vs 23.3%; p<0.001) than HIV uninfected ones. Conversely, both groups have same CACs level. Among HIV-infected patients altered CACs was 30.9%, vs 42.3% among control. Most of HIV-infected patients showed undetectable viremia and high CD4+ count, in parallel with lipid profile disturbances. Conclusion: Increased CAC incidence was associated with age, male gender and PI use among HIV-infected patients. Despite younger, fewer traditional risk factors and with controlled disease, the PLHIV had similar CAC scores compared with controls. Besides viruses itself, antiretroviral drugs play a role, mainly because control viruses at expense of worsening in lipid profile.